The impact of the low-carbon city pilot policy on green innovation in firms - Pei, Fei; Wang, Peilu (Frontiers in Environmental Science, 2022)
To achieve China’s 2030 target for reducing greenhouse gases, the government has implemented a low-carbon pilot city policy. One goal of this policy is to promote the green transformation of local firms; as such, this paper focuses on how the policy influences green innovation among firms. The study analyzed data on the number of green patents held by industrial firms listed in Shanghai and Shenzhen Stock Exchanges in China for the 2007-2017 period. This enabled an investigation of green innovation activity after implementation of the low-carbon pilot city policy, using a Differences-in-Differences model. We found that the low-carbon pilot cities policy has a significant impact on applications for green patents. The relationship is stronger for private owned firms compared to State-owned firms. The direction of the effect was mainly due to green utility patent applications by private owned firms. State-owned firms have strong path dependence and are protected by local governments, so they are less constrained by low-carbon pilot city policies, which makes it difficult for them to improve the green innovation of State-owned firms. Firms in a monopoly position have more motivation to pursue green innovations than firms in competitive settings. Because green innovations have double positive externalities and require cooperation between multiple departments, they are associated with higher risk levels compared to nongreen innovations. It is difficult for firms in highly competitive industries to continuously invest many resources in green environmental R&D. This study provides important data supporting the basis of low-carbon pilot city policy implementation.